Host responses to interspecific brood parasitism: a by-product of adaptations to conspecific parasitism? - Samas, Peter; Hauber, Mark E; Cassey, Phillip; Grim, Tomas (Frontiers in zoology, 2014)
BACKGROUND: Why have birds evolved the ability to reject eggs? Typically, foreign egg discrimination is interpreted as evidence that interspecific brood parasitism (IP) has selected for the host's ability to recognize and eliminate foreign eggs. Fewer studies explore the alternative hypothesis that rejection of interspecific eggs is a by-product of host defenses, evolved against conspecific parasitism (CP). We performed a large scale study with replication across taxa (two congeneric Turdus thrushes), space (populations), time (breeding seasons), and treatments (three types of experimental eggs), using a consistent design of egg rejection experiments (n = 1057 nests; including controls), in areas with potential IP either present (Europe; native populations) or absent (New Zealand; introduced populations). These comparisons benefited from the known length of allopatry (one and a half centuries), with no gene flow between native and introduced populations, which is rarely available in host-parasite systems. RESULTS: Hosts rejected CP at unusually high rates for passerines (up to 60%). CP rejection rates were higher in populations with higher conspecific breeding densities and no risks of IP, supporting the CP hypothesis. IP rejection rates did not covary geographically with IP risk, contradicting the IP hypothesis. High egg rejection rates were maintained in the relatively long-term isolation from IP despite non-trivial rejection costs and errors. CONCLUSIONS: These egg rejection patterns, combined with recent findings that these thrushes are currently unsuitable hosts of the obligate parasitic common cuckoo (Cuculus canorus), are in agreement with the hypothesis that the rejection of IP is a by-product of fine-tuned egg discrimination evolved due to CP. Our study highlights the importance of considering both IP and CP simultaneously as potential drivers in the evolution of egg discrimination, and illustrates how populations introduced to novel ecological contexts can provide critical insights into brood parasite-host coevolution.
Keywords: Species introductions; Coevolution; Heterospecific brood parasitism; Collateral damage; Intraspecific brood parasitism; Discrimination